PERKEMBANGAN INDUSTRI SARUNG TENUN PADA MASYARAKAT DI KELURAHAN SULAA KECAMATAN BETOAMBARI KOTA BAUBAU - Indriani, Noni; Hak, Pendais (Jurusan Pendidikan Sejarah, Universitas Halu Oleo, 2020)
ABSTRACT: The main problem in this journal is how the development of the woven sarong industry in Sulaa Village, Betoambari District, Baubau City, and how the social and economic impacts of woven sarongs on the community in Sulaa Village, Betoambari District, Baubau City. This research method is a qualitative descriptive research method. The data collection techniques used were observation, interview and documentation. The data analysis used in this study is to summarize data, present data, and draw conclusions. The results showed that: (1) The weaving sarong in Sulaa Subdistrict, Betoambari District, Baubau City has experienced a small part of the development both in terms of equipment and materials used, in terms of motifs, weaving craftsmen, to marketing of woven sarongs, (2) woven sarongs have an impact social and economic impacts on people's lives. The resulting social impact is the woven sarong as self-identity and social stratification in society. Meanwhile, the resulting economic impact is that Sulaa is used as a tourist destination for colorful weaving villages that can increase the income of weaving craftsmen.